Transplacental and Breast Milk Transfer of IgG1 Are Both Required for Prolonged Protection of Offspring Against Influenza A Infection - Chronopoulos, Julia; Martin, James G.; Divangahi, Maziar (Frontiers in Immunology, 2022)
The immune system during pregnancy teeters between maintaining fetal tolerance and providing protection against pathogens. Due to this delicate balance, pregnant women and their offspring often have increased susceptibilities to infection. During the first year of life, infant immunity against infection is mainly mediated via passively transferred maternal antibodies. However, our understanding of the route of transfer of the maternal antibodies for conferring protection to influenza A virus (IAV) infection in offspring is incomplete. Here we have demonstrated that offspring from IAV-infected mice were significantly protected against IAV infection. This remarkable increase in survival is mediated via the elevated maternal serum IgG1. By cross-fostering, we further showed that this enhanced host resistance was only achieved in mice born to and nursed by IAV-infected mothers. Collectively, our data suggest that the prolonged protection of offspring against IAV infection requires maternal IgG1 from both the placenta and breast milk.